Samisk nysjamanisme: i dialog med (for)tid og stad. Ein kulturanalytisk studie av nysjamanar sine erfaringsforteljingar – identitetsforhandlingar og verdiskaping. - Fonneland, Trude A. (The University of Bergen, 2010)
This thesis is an exploration of Sami neo-shamanism. Based on interviews, observation, and document analysis it focuses on neo-shamans rooted in North Norway and on their negotiations of identity and narrated experiences. The thesis highlights values being of vital importance in neo-shamans’ self-development and in their marketing of shamanistic products and services. Through my informers’ experience stories and personal myths, I consider three main discourses related to the themes: nature, indigenous people, and the past. All of the themes mentioned appear as pivotal identification models to the informers and to the neo-shamanistic environment. I study how the individual shaman constructs his or her identity with regard to these discourses while at the same time challenging and elaborating them. In my thesis, I seek to throw light upon neo-shamans’ relations to and implementing of nature through their connections with the North Norway scenery. Furthermore I explore how the informers associate with indigenous Sami people and study how the neo-shamans’ ties to Sami culture and traditions serve to legitimise their activities and experiences. I also enlighten the neoshamans’ attachment to selected elements in the past and thereby question how the choice of past has consequences for the present and for the informers’ construction of an identity as neo-shamans. Some of the discourses and tendencies central to the neo-shamanistic milieu also come across as valuable resources for groups outside their environment. Through the thesis I aim to prove how neo-shaman use of and focus on North Norway’s nature and on Sami culture and traditions become part of a cultural and political awareness and are expressed through strategies to enhance identities and marketing of the North Norwegian region with its nature and people.